Development Strategy Digitalization on Tourism Destinations Gunung Tumpa Raya Forest Park H. V. People Regional Technical Implementation Units North Sulawesi Provincial Forestry Service - Dondokambey, Rainier Nicko; Kairupan, Sisca B.; Tuerah, Philoteus (International Journal of Information Technology and Education, 2022)
Business tourist natural held in accordance with principal conservation source power natural life and its ecosystem, for increased utilization uniqueness, peculiarity, beauty nature and/ or beauty type or diversity type wildlife and/ or type plants found in the area asylum wildlife, garden national, park forest highways and parks tour nature. Purpose of this research is intended for do analysis about: Development strategy Forest Mountain Forest Park tour Tumpa HV People as well as knowing Strengths, Weaknesses, Opportunities and Threats for Park development Forest Raya Gunung Tumpa HV People. Method Research use Method Study Qualitative Descriptive in which the data collection techniques consist from interview, observation, and documentation with refers to the SWOT matrix (Strength, Weakness, Opportunity, Threat). From the results study about development destination tour, obtained some strategies as following: Promotion through online media with take advantage of the digital era, Provision of capital and facilities, Communication with community lover natural for promotion and outreach in a manner periodically.